Polarization among Stakeholders Perception on the Interpretation of Ecotourism Resources in Gunung Halimun Salak National Park - Helianthi Dewi; Ricky Avenzora; Dudung Darusman; Cecep Kusmana (Jurnal Manajemen Hutan Tropika, 2022)
The study of polarization of stakeholder perceptions is important to consider the policies that must be taken by area managers related to the development of interpretation programs in national park areas. This study was aimed to analyze and evaluate the characteristics of the subject of interpretation that are considered important by stakeholders, to analyze the differences in perceptions among stakeholders of the attractiveness of the subject of interpretation and to determine the polarization of perceptions of the subject of interpretation among stakeholders in relation to the management of Gunung Halimun Salak National Park (GHSNP). Stakeholder perception data was obtained by distributing a closed pattern questionnaire. Cluster analysis was used to determine the variety of stakeholder perception in interpretation subjects within the GHSNP area. As for knowing the direction and scale of the polarization of stakeholder perceptions, it was analyzed by Kruskal Wallis and Mann Whitney test. The results showed that the largest polarization among stakeholders occurred in the cultural subjects, and the direction of polarization was negative. This indicates the weak attractiveness of the subject of cultural interpretation to stakeholders. The greater commonality of perception between the community and managers forms the basis for the development of cultural interpretations. This development is expected to bridge the community's needs for the GHSNP area as well as provide stronger support for the management of the national park area.